2016
DOI: 10.21646/bilimname.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Şiddet ve Kişilik İlişkisi Üzerine Psikolojik Bir Araştırma

Abstract: Şiddet konusu üzerine yapılan araştırmaların ortak vurgusu şiddetin son derece karmaşık ve çok boyutlu bir olgu olduğudur. Bu çalışma ile de şiddete ilişkin boyutlardan birisi olduğu varsayılan kişilik özellikleri üzerinde durulacaktır. Bu anlamda ilk olarak şiddet kavramı ortaya konulmaya çalışılacak ve literatür değerlendirmesine yer verilecektir. Sonrasında ise kişilik konusuna değinilecek ve kişilik konusunda ortaya çıkan yaklaşımlar tartışılacaktır. Daha sonra her iki değişken arasındaki ilişki üzerine ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
2
4
0
5
Order By: Relevance
“…Our study found that male students had a "higher" violence tendency and gender affected violence tendency. This result is in parallel with other studies (Ameri et al 2017;Karayağız Muslu et al,2020;Ulu, 2016;Yüksel et al 2015). There are studies which indicate that physical aggression is environment-related for females and geneticsrelated for males (McDermott and Hatemi, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study found that male students had a "higher" violence tendency and gender affected violence tendency. This result is in parallel with other studies (Ameri et al 2017;Karayağız Muslu et al,2020;Ulu, 2016;Yüksel et al 2015). There are studies which indicate that physical aggression is environment-related for females and geneticsrelated for males (McDermott and Hatemi, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Being witness or subject to domestic violence during childhood constitutes a risk factor for crimes of violence. Being witness or subject to domestic violence and stereotypical gender roles in society can form a basis for crimes of violence (Ulu, 2016). It is possible that individuals who witness violent behaviors within the family or become subjected to or witness violence later on consider using violence as feasible.…”
Section: The Relation Between Traits and Violence In Nursing Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ailenin sosyoekonomik düzeyinin düşük olması, aile içinde şiddete tanıklık etmek veya maruz kalmak (Heitmeyer ve Hagan, 2005) anne baba arasındaki geçimsizlik, anne ve babanın erken yaşta çocuk sahibi olması, çocuk sayısının fazlalığı, aile üyeleri arasındaki bağın kopuk olması (Krug ve ark., 2002) ailede suça eğilimin yüksek olması, çocuğa yeterli ilginin gösterilmemesi ve çocuğa kötü davranılması (Hawkins ve ark., 2000) ebeveynin yetersiz gözetim ve yönlendirmesi, tutarsız anne baba tutumu (Ögel, Tarı ve Yılmazçetin-Eke, 2005), çocuğun istismarı ya da reddi (Ulu, 2016), aile ortamında alkol ve madde kullanımı (Özcebe, 2006) şiddetin ortaya çıkmasında etkili olabilecek aile ile ilgili faktörlerdir.…”
Section: B şIddetunclassified